The Role of E Servicescape on Trust and Purchase Intention of Orami Customers in Bandung - Ian Zulfikar (Sean Institute, 2021)
This study intends to test and explain the effect of visual appeal, layout and function, and financial stability on website trust, as well as to test and explain the relationship between website trust and customer purchase intentions on the orami.co.id website in Bandung. This study's population consisted of all Bekasi-area website visitors from orami co.id who have purchased things online. This study employs a quantitative approach and survey methodology. With the assistance of SPSS 25.0 for Windows, hypothesis testing was used to analyze the data. 1) There was a positive and significant influence of the visual appeal variable on website trust, according to the findings of the study. 2) the function layout variable had a favorable and significant effect on website trust 3) the financial security variable has a positive and significant effect on trust in the website, and 4) the trust variable has a positive and substantial effect on orami.co.id consumer purchase intentions.